Iron-Catalyzed Synthesis of (E)-β-Vinylsilanes via a Regio- and Stereoselective Hydrosilylation from Terminal Alkynes - Liu, Zhi-Kai; Zhang, Guo-Liang; Li, Ding-Chang; Yang, Ying; Chen, Li; Zhan, Zhuang-Ping (Synlett, 2019)
A concise strategy for the synthesis of vinylsilanes from an iron-catalyzed regio- and stereoselective hydrosilylation of terminal alkynes has been developed. The catalyst and reagents are commercially available and easy to handle, providing a simple and practical method for iron-catalyzed anti-Markovnikov hydrosilylation with a good functional group tolerance.
Keywords: vinysilanes; hydrosilylation; terminal alkynes; iron catalyst; synthetic methods